Additive serotonergic genetic sensitivity and cortisol reactivity to lab-based social evaluative stress: Influence of severity across two samples. (August 2022) - Vrshek-Schallhorn, Suzanne; Corneau, Gail M.; Grillo, Alessandra R.; Sapuram, Vaibhav R.; Plieger, Thomas; Reuter, Martin
Abstract: Prior work demonstrates that an additive serotonergic multilocus genetic profile score (MGPS) predicts amplified risk for depression following significant life stress, and that it interacts with elevations in the cortisol awakening response to predict depression. The serotonin system and HPA-axis have bidirectional influence, but whether this MGPS predicts acute cortisol reactivity, which might then serve as a mechanism for depression, is unknown. Our prior work suggests that depression risk factors predict blunted cortisol reactivity to explicit negative evaluative lab-based stress. Thus, we hypothesized that a 4-variant serotonergic MGPS (three SNPs from the original 5-variant version plus 5HTTLPR) would predict blunted cortisol reactivity to explicit negative evaluative stress versus a control. In Sample 1, growth curve modeling showed that the MGPS predicted heightened cortisol reactivity ( p = 0.0001) in an explicitly negative evaluative Trier Social Stress Test variant (TSST) versus a control condition among non-depressed emerging adults ( N = 152; 57% female). In Sample 2, 125 males completed the Socially Evaluative Cold Pressor Test (SECPT), an ambiguously negative evaluative manipulation; findings displayed a similar pattern but did not reach statistical significance ( p s.075–.091). A participant-level meta-analysis of the two samples demonstrated a significant effect of negative evaluation severity, such that the MGPS effect size on reactivity increased linearly from control to SECPT to an explicitly negative evaluative TSST. Findings indicate that this MGPS contributes to sensitivity to social threat and that cortisol dysregulation in the context of social stress may be one mechanism by which this MGPS contributes to depression. Highlights: A serotonergic genetic score has been linked to depression, but cortisol reactivity is untested. In Sample 1, this score predicted greater reactivity to explicit negative evaluation vs. a control. In Sample 2, this score approached significance predicting greater reactivity to a cold pressor test. Three levels of negative evaluative threat facilitated combined analyses of the two samples. Combined tests link this serotonergic genetic score with sensitivity to negative evaluation.